Culture-based Animation: Inserting Indonesian Local Culture in Animation Series ‘Si AA’ - Tira Nur Fitria (Journal of Language and Literature, 2022)
Indonesia offers many opportunities to use local culture’s potential in producing Indonesian animation. The greatest idea is to make an animation that is based on the characteristics of traditional or local arts from each region. This research analyzes the Indonesian local cultures inserted in the animation series Si Aa’ created by RANS Animation Studio. This research uses descriptive qualitative research. The documents are taken from 9 videos of the animation series “Si Aa” released in 2020 and 2021. The result analysis shows that there are 12 examples of Indonesian local culture in ‘Si Aa” animation series such as 1) Inserting a local language “Sundanese”, 2) Inserting local story (folklore) of Timun Emas, 3) Inserting regional Dance “Jaipong”, 4) Inserting regional musical instruments “Angklung”. 5) Inserting regional music instrument “Gamelan”. 6) Telling an Indonesian national hero “Kapitan Pattimura”. 7) Showing a palace building “Keraton”. 8) Inserting regional performing arts “Wayang Suket”. 9) Inserting regional Performing Arts “Ondel-ondel”. 10) Inserting traditional game “Gangsing”, 11) Inserting local handicraft “Tenun”, 12) Showing tourism place destination in Maluku, 13) Inserting local custom “Tandur”. Through animation, the creator conveys the local culture by recognizing and appreciating an Indonesian identity in their work. Initially, culture-based animation served simply as a means of Indonesian cultural preservation.